Pachymeningeal involvement in POEMS syndrome: MRI and histopathological study. Issue 1 (7th June 2011) - Briani, Chiara; Fedrigo, Marny; Manara, Renzo; Castellani, Chiara; Zambello, Renato; Citton, Valentina; Campagnolo, Marta; Torre, Chiara Dalla; Lucchetta, Marta; Orvieto, Enrico; Rotilio, Antonino; Marangoni, Sabrina; et al.
Abstract : Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, skin changes (POEMS) syndrome is a rare plasma cell disease. Vascular endothelial growth factor (VEGF) seems to play a pathogenic role. Peripheral neuropathy is the main neurological feature. Cranial pachymeningitis has occasionally been reported, but no histopathological studies have been performed. The authors extensively evaluated the central nervous system MRI in 11 patients (seven men, four women; mean age at diagnosis 54.45 years) with POEMS syndrome. In two patients, meningeal histopathology with staining for VEGF and VEGF receptor was performed, and pachymeningeal involvement characterised at histopathological, immunohistochemical and confocal microscopy levels. Nine patients presented with cranial pachymeningitis. One patient suffered from migraine, and none complained of cranial nerve palsies or visual loss. None showed any MRI signs of spinal pachymeningitis. No correlation was found with disease duration and VEGF serum level. Histopathology showed hyperplasia of meningothelial cells, neovascularisation and obstructive vessel remodelling, without inflammation. VEGF and VEGF receptor were strongly coexpressed on endothelium, smooth-muscle cells of arterioles and meningothelial cells. In conclusion, POEMS patients present a high prevalence of meningeal involvement. The histological changes, different from those present in chronic pachymeningitis of other aetiology, suggest a possible VEGF role in the pathogenesis of the meningeal remodelling.